Impact of COVID-19 on medical treatment patterns in gynecologic oncology: a MITO group survey. Issue 10 (23rd August 2021) - Cioffi, Raffaella; Sabetta, Giulia; Rabaiotti, Emanuela; Bergamini, Alice; Bocciolone, Luca; Candotti, Giorgio; Candiani, Massimo; Valabrega, Giorgio; Mangili, Giorgia; Pignata, Sandro
Abstract : Objective: COVID-19 is a global public health emergency. The increasing spread of COVID-19 presents challenges for the clinical care of patients with gynecological tumors. The Multicenter Italian Trials in Ovarian cancer and gynecologic malignancies (MITO) performed a survey to evaluate the impact of the COVID-19 pandemic on medical treatment of gynecological cancer, with a focus on chemotherapy and oral treatment with poly(ADP)-ribose polymerase inhibitors (PARP-i). Methods: The survey consisted of a self-administered online questionnaire, sent via email between November 2020 and January 2021 to all members of MITO group. Results: Forty-nine centers completed the questionnaire. The majority of respondents (83%) use screening tests to determine COVID-19 status in patients who were to undergo chemotherapy or oral medications. All respondents to our survey continued cancer therapy in patients who tested negative for COVID-19 during the pandemic. Seventy-three percent of respondents declared they stopped treatment with chemotherapy or PARP-i only after a positive swab and resumed therapy when negative tests were confirmed. Conclusions: COVID-19 positivity impacted patterns of treatment in patients diagnosed with ovarian cancer within the MITO group. Further investigations are needed to evaluate whether these modifications influence oncological clinical outcomes.